Blood Transfusion During Total Ankle Arthroplasty Is Associated With Increased In-Hospital Complications and Costs. Issue 2 (April 2019) - Ewing, Michael A.; Huntley, Samuel R.; Baker, Dustin K.; Smith, Kenneth S.; Hudson, Parke W.; McGwin, Gerald; Ponce, Brent A.; Johnson, Michael D.
Introduction. Total ankle arthroplasty (TAA) is an increasingly used, effective treatment for end-stage ankle arthritis. Although numerous studies have associated blood transfusion with complications following hip and knee arthroplasty, its effects following TAA are largely unknown. This study uses data from a large, nationally representative database to estimate the association between blood transfusion and inpatient complications and hospital costs following TAA. Methods. Using the Nationwide Inpatient Sample (NIS) database from 2004 to 2014, 25 412 patients who underwent TAA were identified, with 286 (1.1%) receiving a blood transfusion. Univariate analysis assessed patient and hospital factors associated with blood transfusion following TAA. Results. Patients requiring blood transfusion were more likely to be female, African American, Medicare recipients, and treated in nonteaching hospitals. Average length of stay for patients following transfusion was 3.0 days longer, while average inpatient cost was increased by approximately 50%. Patients who received blood transfusion were significantly more likely to suffer from congestive heart failure, peripheral vascular disease, hypothyroidism, coagulation disorder, or anemia. Acute renal failure was significantly more common among patients receiving blood transfusion ( P < .001). Conclusion. Blood transfusions following TAA are infrequent and are associated with multiple medical comorbidities, increased complications, longer hospital stays, and increased overall cost. Levels of Evidence: Level III: Retrospective, comparative study